Enhanced Bioaccessibility and Antioxidant Activity of Curcumin from Transglutaminase Cross-Linked Mulberry Leaf Protein-Stabilized High-Internal-Phase Pickering Emulsion: In Vivo and In Vitro Studies - Yingshan Xie; Hongyan Li; Zeyuan Deng; Yanfang Yu; Bing Zhang (Foods)
The objective of this study was to formulate Pickering emulsions stabilized by transglutaminase cross-linked mulberry leaf protein (TG-MLP) nanoparticles as a delivery system for curcumin (Cur) and to assess its bioaccessibility both in vivo and in vitro. The encapsulation efficiency of curcumin in high-internal-phase Pickering emulsions (HIPEs) prepared at pH 10 with a 20 mg/mL concentration of TG-MLP reached 93%. Compared to Oil-Cur, Cur-HIPEs exhibited superior antioxidant activity. Furthermore, Cur-HIPEs demonstrated enhanced stability against ultraviolet irradiation, storage under dark and visible light, and heating, in contrast to Oil-Cur. Among the various conditions tested, HIPEs stabilized by TG-MLP nanoparticles at an ionic strength of 1000 mM offered the most effective protection for curcumin. Moreover, TG-MLP nanoparticles at pH 8 provided better stability for the formulated HIPEs compared to those at pH 6 and 10. During simulated gastrointestinal digestion, the bioaccessibility of curcumin in Cur-HIPEs was significantly increased to 30.1% compared to Oil-Cur. In murine studies, higher levels of curcumin were detected in the stomach, small intestine, rectum, ileum, and feces following administration of Cur-HIPEs, indicating improved protection, absorption, and potential biological activity during digestion. Consequently, HIPEs offer excellent protection and delivery for curcumin during digestion.